March madness in Wall Street: (What) does the market learn from stress tests? - Fernandes, Marcelo; Igan, Deniz; Pinheiro, Marcelo (Journal of Banking & Finance, 2020)
Annual stress tests have become a regular part of the supervisors’ toolkit following the global financial crisis. We investigate their market implications in the United States by looking at price and trade reactions as well as information asymmetry and uncertainty indicators around the tests, and bank behavior after the tests. The evidence we present supports the notion that there is important new information in stress tests. This is particularly the case during crisis. Moreover, public disclosure appears not to adversely affect informational asymmetries and uncertainties. Importantly, public disclosure of stress test results (and methodology) does not seem to have reduced private incentives to generate information or to have led to distorted incentives.